Pedagogy of the heart: grammar, philosophy, and the Christian reader in Origen's Greek homilies on the psalms - Solheid, John ca. 20./21. Jh. (Vigiliae Christianae, 2025)
"This monograph presents a detailed and accessible analysis of the recently discovered Greek Homilies on the Psalms preached by Origen in the late 240's CE. The author brings a discerning eye to the interplay of Hellenistic paideia and Origen's exegetical and pedagogical aims of creating a Christian reading culture. In so doing, he also challenges the traditional dichotomy of school and church in the third century. The reader will discover Origen the teacher applying the critical tools of his time in order to cultivate the Christian reader in purity of heart"--